Fresno County Bar Association Legislators' Reception at The Downtown Club - Watkins, Howard::::::::: (1988)
Supervisor Juan Arambula, Robert Wilkinson, and Vincent McGraw at buffet table Lee Snyder and Hagop Bedoyan in background